A trend of proliferation of proleptic shoots in partial populations of Scots pine - J. Nárovcová; V. Nárovec (Journal of Forest Science, 2010)
The incidence of the summer (late-seasonal) growth of shoots was monitored following the planting of Scots pine from different provenances of the Czech Republic and different planting regimes in an experimental plot in Týniště nad Orlicí. In the third year after reforestation the local populations had the highest proportion of summer growth of the shoots (18%) compared to other populations. From the second to the fourth year after planting the percentage proportion of summer shoots was determined for the species Scots pine in conditions of the Polabí region, it was 13.5% of the individuals in each year. The analysis of stem sections demonstrated double rings as a result of the cambium activation through the growth of summer shoots.